Comparison of maxillary setback by maxillary tuberosity removal or intentional pterygoid plate fracture in Le Fort I osteotomy: a long-term evaluation. Issue 4 (April 2021) - Xiang, Z.; Wang, Y.; He, Y.; Wang, Y.; Bi, R.; Li, J.
Abstract: The purpose of the study was to investigate the clinical application and long-term stability of maxillary setback in Le Fort I osteotomy using maxillary tuberosity removal or intentional pterygoid plate fracture (IPPF). Eighty adult class II patients who underwent Le Fort I osteotomy with bilateral sagittal split ramus osteotomy by the same surgeon between January 2013 and January 2019 were included in this retrospective study. Traditional maxillary tuberosity removal was performed in 40 patients (group I), and the other 40 patients (group II) underwent IPPF to set back the maxilla according to surgeon preference. An obvious change in profile was observed for all of the patients, with no significant relapse at 1 year postoperative. The operation time and intraoperative blood loss were significantly higher in group I than in group II ( P = 0.037 and P = 0.021, respectively). In group II, the most superior point of the fracture line was at a mean distance of 12.25 ± 2.04 mm above the most inferior point of the pterygoid plate. More bone fragments were noted when the fracture level was low than when it was high. In conclusion, both maxillary tuberosity removal and IPPF resulted in sufficient and stable maxillary setback, with IPPF showing less blood loss and a shorter operative time.